A structural equation model of green supply chain management practices and firm performance. - ML Tseng (Journal of the philippine institute of industrial engineers)
Globalization results in both pressure and drivers for Taiwanese enterprises ti improve their SCM practices and further to improve their firm performance. Supply chain management (SCM) involves integration, co-ordination and collaboration across organizations and throughout the supply chain. This paper analyses the relationship among strategic purchasing, reverse logistics, manuafcturing strategy, supply chain management practices and firm performance. This framework is then tested on a sample of seventy firms at Three C's electronic manufacturing industry in Taiwan. The methods were through descriptive analysis, Factor analysis and multiple regression analysis to identify the relationship among the variables. The results show significant relationships in the framework with closed model. They support the argument found in the literatures that reverse logistics, strategic purchasing, manufacturing startegy and supply chain management have significant positively related to firm performance. The direct and indirect impact coefficients were estimated. Implications of the findings are discussed.